1958
DOI: 10.1136/bmj.2.5104.1068
|View full text |Cite
|
Sign up to set email alerts
|

Jaundice Associated with Administration of Iproniazid

Abstract: situation on the basis of the number of anginal attacks and the effort required to produce them. It should always be stopped before the patient returns to work.Because of the danger of masking myocardial ischaemia, the numerous side-effects, and the risk of serious liver damage, iproniazid is not indicated for the patient with mild angina.Although the drug could theoretically give rise to "silent infarction," this did not happen in any of our patients. Two of them had infarcts while receiving iproniazid. Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

1959
1959
1965
1965

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…No case history could be found in the literature in which so small a dose of iproniazide caused a fatal result. Floody, Dixon, and Mattia (1958) state that the amount of iproniazide given to 13 fatal cases ranged from 300 to 8,000 mg. They give no details and most of the information seems to have been obtained from questionnaires.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No case history could be found in the literature in which so small a dose of iproniazide caused a fatal result. Floody, Dixon, and Mattia (1958) state that the amount of iproniazide given to 13 fatal cases ranged from 300 to 8,000 mg. They give no details and most of the information seems to have been obtained from questionnaires.…”
Section: Discussionmentioning
confidence: 99%
“…They give no details and most of the information seems to have been obtained from questionnaires. Benaim and Dixon (1958) quote Marks as saying that jaundice may occur with as little as 25 mg. and that the duration of therapy is not important.…”
Section: Discussionmentioning
confidence: 99%
“…C liniquem ent et biologiquem ent, la ressem blance est égalem ent étroite. D 'autres auteurs [7,44,83] ont ra p p o rté des cas sem blables oii l'a tte in te liépato-cellulaire é ta it au p re m ier plan.…”
Section: Foie Et Traitement Antibacillaireunclassified
“…Senior Registrar From the University Department of Cardiology, Manchester Royal Infirmary Considerable success has been claimed for iproniazid in the treatment of angina pectoris (Cesarman, 1957;Cossio, 1957Cossio, , 1958Master, 1958;Towers and Wood, 1958). More recently, however, controlled trials have shown that the response to iproniazid may be little or no better than to a placebo (Dewar et al, 1959;Snow and Anderson, 1959).…”
mentioning
confidence: 99%
“…More recently, however, controlled trials have shown that the response to iproniazid may be little or no better than to a placebo (Dewar et al, 1959;Snow and Anderson, 1959). Moreover, it has unpleasant and sometimes serious side-effects, particularly when used for prolonged periods (Robitzek and Selikoff, 1952;Master, 1958;Towers and Wood, 1958;Benaim and Dixon, 1958). Its most powerful known pharmacological action is the inhibition of monoamine oxidase, and it is thought that some or all of its clinical effects may be due to this. "…”
mentioning
confidence: 99%